A pilot study to evaluate the safety and efficacy of treprostinil in the treatment of calcinosis in systemic sclerosis. (29th October 2021) - Chung, Melody P; Valenzuela, Antonia; Li, Shufeng; Catanese, Benjamin; Stevens, Kate; Fiorentino, David; Strand, Vibeke; Chung, Lorinda
Abstract: Objectives: We evaluated the safety and efficacy of oral treprostinil in preventing progression of SSc-associated calcinosis. Methods: This prospective open-label study enrolled 12 SSc patients meeting 2013 ACR/EULAR classification criteria with confirmed clinical and radiographic evidence of one or more calcinosis deposit in the hands. Patients received oral treprostinil for 1 year. Primary endpoints were safety/tolerability and percentage of patients without radiographic progression of calcinosis at 1 year (<25% increase in Scleroderma Clinical Trials Consortium radiographic score). Secondary endpoints included 1-year changes in Scleroderma HAQ (SHAQ), Cochin Hand Functional Scale, Medical Outcomes Survey Short Form 36 (SF-36), Raynaud Condition Score and patient/physician assessment of calcinosis severity. Results: Twelve female patients were enrolled, half with diffuse cutaneous disease; median age was 55 years (range 35–68 years). Five patients completed the study. Seven patients withdrew due to intolerable adverse effects ( n  = 3), intercurrent unrelated illness ( n  = 2, cirrhosis, cancer), progressive SSc ( n  = 1) and personal reasons ( n  = 1). Most patients developed headaches and gastrointestinal adverse effects. Four of 11 (36%) patients with 1-year follow-up hand radiographs experienced progression of calcinosis. Of five who completed treatment, calcinosis was stable in four (80%) with progression in one. Based on SF-36 Physical and Mental Component and Domain scores, transition question and SF-6D utility score, all patients who finished the trial reported overall improvement or no change compared with baseline. Conclusion: Oral treprostinil was poorly tolerated in SSc patients with calcinosis. Of five patients who completed treatment, most (80%) had documented stability of calcinosis on hand radiographs at 1 year. ClinicalTrials.gov identifier: NCT02663895.